Participation of school health nurse in care of abused child in school and family — case study - Kram, Mirosława; Pruszak, Emilia; Zreda-Pikies, Aneta; Wróbel- Bania, agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. According to the definition, the term “abused child” indicates the perpetrators of abuse; they might be: adults, peers and institutions that intended or unintended action deranges the child’s development and in extreme cases leads to his or her death. Aim of the study. The aim of the study was to demonstrate the phenomenon of child abuse in school and family and to demonstrate participation of school health nurse in care of an abused child Material and methods. The study was conducted in the school year 2011/12 among the first class of high school students. As the research method was used “case study”. The research techniques used: interview/conversation, observation and analysis of documents. The research tool was a “Charter of nursing history in the educational environment”. Results and conclusions. The school nurse is one of the first people who might be able to recognize signs of child abuse. The school nurse is actively involved in the interdisciplinary care of abused child.